Analisis Resepsi Pejabat Publik terhadap Program Update Pagi SBO TV - Ardiani Kusuma Sari; Didik Hariyanto (Kanal: Jurnal Ilmu Komunikasi, 2016)
This study aims to describe the reception of public officials on Update Pagi SBO TV program. This research using qualitative method. Informants in this study are public officials who come from government or non government in Surabaya. The data collected by indepth interviews, observation and documentation. Data analysis techniques used Miles and Huberman models. The results of the study shows that the Update Pagi program is considered important and effective, it is helpful in providing information from stakeholders to the public, and has contributed to delivering new policies or problem solving with a direct dialogue strategy between the community and the government or parties related themes discussed in Update Pagi SBO TV Program.